HAK DAN KEWAJIBAN SUAMI ISTRI PADA KELUARGA TKI DI DESA TRESNOREJO, KEBUMEN, JAWA TENGAH: ANTARA YURIDIS DAN REALITA - Suratno, Dwi; Syafei, Ermi Suhasti (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
The phenomenon of husband or wife working as Indonesian Labor (TKI) is not a new among people of Tresnorejo village, Kebumen, Jawa Tengah. The reason they work as TKI is to improve the welfare of households, because Tresnorejo’s villager income still low. Their job they rely on is making a caping - Asian conical hat made of plaited bamboo. In Islamic law, the husband requires to give his wife and family needs, like clothing, food and house. Wife is not forbidden to work in order to help her husband earning a living for the family. On the basis of voluntary work of his wife, the work considered charity for the husband . The implementation of the rights and obligations between husband and wife in the family did not violate Islamic law, because of the balance between madārat and maslahah, but it could also result in a negative on the family. Islamic law does not forbid, his wife helped work to earn a living for the family. On the basis of voluntary work with his wife, then considered the husband wife charity. Implementation of the fulfillment of the rights and obligations of husband and wife in the family did not violate Islamic law, TKI, as between madārat and maslahah it is balanced, but it could also result in a negative impact on the family.[Fenomena suami atau istri bekerja sebagai TKI bukanlah fenomena baru bagi masyarakat Desa Tresnorejo. Faktor yang mendorong suami atau istri bekerja sebagai TKI adalah ingin meningkatkan kesejahteraan rumah tangga. Hal ini disebabkan oleh penghasilan warga Desa Tresnorejo yang masih kurang (hanya mengandalkan hasil dari pertanian dan usaha membuat tudung—caping yang terbuat dari anyaman bambu). Hukum Islam mewajibkan suami untuk menafkahi istri dan keluarganya; mulai dari sandang, pangan sampai papan. Hukum Islam tidak melarang, istrinya membantu bekerja mencari nafkah untuk keluarga. Atas dasar istrinya bekerja dengan sukarela, maka dianggap sedekah istri kepada suami. Pelaksanaan pemenuhan hak dan kewajiban suami istri pada keluarga TKI tidak melanggar hukum Islam, karena antara madārat dan māslahah itu seimbang, namun hal tersebut juga bisa mengakibatkan dampak negatif pada keluarga.]